Intracytoplasmic sperm injection with assisted oocyte activation resulting in successful pregnancies and live birth in couples with globozoospermia: A report of two cases - Puneet Kaur Kochhar; Pranay Ghosh (Journal of Human Reproductive Sciences, 2018)
Globozoospermia, characterized by round-headed acrosomeless sperm, is a rare and severe form of teratozoospermia. We report a successful pregnancy in two cases of total globozoospermia after intracytoplasmic sperm injection (ICSI) with oocyte activation with calcium ionophore. In the first case, globozoospermia was diagnosed on the day of oocyte retrieval. Among 11 retrieved oocytes, only one fertilized after ICSI. The pregnancy test 2 weeks after embryo transfer was negative. Two months later, the patient underwent ovarian stimulation again. The 12 retrieved oocytes were exposed to calcium ionophore medium following ICSI. Four oocytes were fertilized and two blastocysts were transferred resulting in a clinical pregnancy. In the second case, among seven retrieved oocytes, three fertilized after ICSI and assisted oocyte activation, and two 8-cell embryos were transferred, resulting in a positive pregnancy. The successful outcome here justifies the use of ICSI with oocyte activation to improve the pregnancy rate significantly when dealing with globozoospermia.